2013
DOI: 10.1007/s00109-013-1019-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of neovascularization and resistance to anti-angiogenic therapies in glioblastoma multiforme

Abstract: Glioblastoma Multiforme (GBM) is the most malignant brain tumor and highly resistant to intensive combination therapies. GBM is one of the most vascularized tumors and vascular endothelial growth factor (VEGF) produced by tumor cells is a major factor regulating angiogenesis. Successful results of preclinical studies of anti-angiogenic therapies using xenograft mouse models of human GBM cell lines encouraged clinical studies of anti-angiogenic drugs such as bevacizumab (Avastin), an anti-VEGF antibody. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
102
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 102 publications
(117 reference statements)
1
102
0
3
Order By: Relevance
“…While tumor cells initially grow along pre-existing blood vessels, tumor progression is accompanied by an increase in angiogenesis, mediated primarily through the cytokine vascular endothelial growth factor (VEGF) [2,3]. As tumors grow and normal vasculature is disrupted, hypoxic conditions induce endothelial cells and tumor cells to express VEGF and proangiogenic transcription factors, promoting vascular remodeling and sprouting [2,[4][5][6]. Importantly, increased VEGF expression has been shown to correlate with higher tumor grade and decreased patient survival [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While tumor cells initially grow along pre-existing blood vessels, tumor progression is accompanied by an increase in angiogenesis, mediated primarily through the cytokine vascular endothelial growth factor (VEGF) [2,3]. As tumors grow and normal vasculature is disrupted, hypoxic conditions induce endothelial cells and tumor cells to express VEGF and proangiogenic transcription factors, promoting vascular remodeling and sprouting [2,[4][5][6]. Importantly, increased VEGF expression has been shown to correlate with higher tumor grade and decreased patient survival [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Bevacizumab is a humanized monoclonal antibody that neutralizes circulating VEGF, preventing its interaction with VEGF receptors and subsequent angiogenesis through tumor vessel formation [2,9]. While bevacizumab is the first antiangiogenic therapy approved for the treatment of recurrent GBM, results in clinical trials have been mixed [10].…”
Section: Introductionmentioning
confidence: 99%
“…GBM is the most malignant primary brain tumor and secretes high levels of vascular endothelial growth factor, inducing vascular proliferation. Despite its vascular density, GBM is highly resistant to chemotherapy and antiangiogenic therapies (11). Comparison of postchemotherapy biopsies of GBM with our model addresses questions of how tissue architecture and vascular distribution influence chemotherapeutic delivery in addition to validating the generality of our modeling approach.…”
mentioning
confidence: 99%
“…Glioma, which is the most common intracranial tumor in adults, is characterized by high vascularization and invasive capacity, as well as peritumoral brain edema (PTBE) (1)(2)(3)(4). In preoperative magnetic resonance imaging (MRI), the degree and morphological characteristics of PTBE vary between different types of glioma (5).…”
Section: Introductionmentioning
confidence: 99%
“…In preoperative magnetic resonance imaging (MRI), the degree and morphological characteristics of PTBE vary between different types of glioma (5). PTBE, which facilitates glioma cell invasion and significantly affects patient prognosis, is a major cause of the high disability and mortality rate of glioma (4,6). A previous study has demonstrated that glioma recurrence patterns are affected by the degree and morphological characteristics of PTBE (7).…”
Section: Introductionmentioning
confidence: 99%